Enhancing mathematical literacy through the integration of PBL and CRT: A Case study of grade X - Ricky Mardianto; Vera Dewi Susanti; Yuliana Endang Sulastri (Program Studi Pendidikan Matematika, Universitas Nusantara PGRI Kediri, 2025)
This research aims to understand the application of Problem-Based Learning model with a Culturally Responsive Teaching approach in improving students’ mathematical literacy. The research method implemented is Classroom Action Research (CAR), which is carried out in four stages: 1) planing, 2) implementation, 3) observation, and 4) reflection. The subjects of this research are 35 students from class X TPM 2 at SMKN 1 Madiun. The data collection techniques used are observation and tests. The observation technique is used to observe student activities during classroom learning. The test technique is used to collect data on student’s mathematical literacy abilities. The data analysis technique used in this research is descriptive statistical analysis. Students’ literacy skills showed an average score of 55,54 in Cycle 1 with a learning mastery of 37,14%, which increased to an average of 81,40 with a learning mastery of 77,14% in cycle 2. It can be concluded based on the data analysis results that the Problem-Based Learning model with a Culturally Responsive Teaching approach can imporve the mathematical literacy skills of class X students at SMKN 1 Madiun.